THE TRANSLATION STRATEGIES OF ENGLISH IDIOM INTO INDONESIAN IN THE NOVEL “THE ADVENTURE OF THE SPECKLED BAND SHERLOCK HOLMES BY SIR ARTHUR CONAN DOYLE” - La Ucha Elliana Walliddaena (Sinar Lima, 2024)
This research aimed to discover the translation strategies used to find out the types of idioms in the novel The Adventure of the Speckled Band Sherlock Holmes by Sir Arthur Conan Doyle. This research was based on two theories, Baker's theory to discover the translation strategies used as follows; Using an idiom of dissimilar meaning and form, using dissimilar meaning but dissimilar form, translation by paraphrase, and translation by omission. Also, use McCharty and O’Dell’s theory to find out the types of idioms: Similies, binomials, proverbs, euphemisms, cliches and fixed statements, and other languages. The method used in this research was the descriptive qualitative method and the research design was library research. For collecting the data, there are five steps, they are; close reading, identification, note-taking, classification, and coding to get valid data. As a result of the research, it was found that there are fifty-eight idioms data found in The Adventure of The Speckled Band Sherlock Holmes By Sir Arthur Conan Doyle. Meanwhile, the most preferred strategies used by the translator in translating the idioms in the novel The Adventure of Speckled Band Sherlock Holmes by Sir Arthur Conan Doyle is strategies translating by omission and the most idioms used in the novel The Adventure of The Speckled Band Sherlock Holmes by Sir Arthur Conan Doyle is cliche and fixed statements.